Studies of RF Shimming Techniques with Minimization of RF Power Deposition and Their Associated Temperature Changes - Tang, Lin (2011)
In ultrahigh field (UHF), human magnetic resonance imaging (MRI) concerns related to the homogeneity of the [Formula: see text] field [the radiofrequency (RF) magnetic field component responsible for the excitation of the spins] and the local/average specific absorption rate (SAR) are highly evident. In this work, through RF shimming techniques, a full-wave electromagnetic model that treats a coupled-RF coil and the load (an 18-tissue anatomically detailed human head model) as a single system is utilized to simultaneously (1) improve the homogeneity of [Formula: see text] field in various regions of interest across the volume of the human head and (2) minimize the total RF power deposition at 7 and 9.4 T. The numerical results illustrate that the [Formula: see text] field homogeneity (evaluated by the coefficient of variance) can be greatly improved in 3D slabs that vary in orientations and sizes, in the brain, and in the entire head volume without increasing the total RF power deposition in the head to exceed that obtained with quadrature excitation. The RF shimming simulation results are experimentally validated (by performing RF shimming without experimental B(1) measurements) on a head-sized phantom using a 7-T human MRI scanner equipped with a transmit array excitation system. The SAR and associated temperature changes under quadrature and RF shimming excitation conditions are calculated and compared.